DAYA TERIMA COOKIES TEPUNG RIMPANG BUNGA TASBIH (Canna edulis Ker.) DAN TEPUNG IKAN PATIN (Pangansius hypopthalmus - Melisa .; Etti Sudaryati; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Beads flower (Canna edulis Ker.) was sweetless arrowroot with lower carbohydrate (22,6%). Catfish (Pangansius hypopthalmus) was one of incantations fish with upper protein. This research discussed of cookies formulated by Beads flower rhizome flour (Canna edulis Ker.) and Catfish flour (Pangansius hypopthalmus) as a selected nutrient-rich snack where maintain the nutrient status of the community. The aim of the research was to get ideal cookies with nutrient content and determine the most preferred by community. This research used organoleptic assessment using hedonic scale. The object consisted four cookies formulation with beads flower rhizome flour (75% and 80%) and catfish flour (20% and 25%). Two from the four samples added to wheat-flour (5%) as a comparison of organoleptic test. Instrument of data collect used panelist by incidental sampling. The method analysis of organoleptic used paired analysis of variance (Repeated ANOVA Test) and descriptive analysis by percentage. The results stated the acceptance panelist byscored mean cookies obtained the best treatment was showed from cookies2 with combination additionof beads flower rizhome flour 75%, catfish flour 20% and wheat-flour 5%.Cookies2 were preferably in terms of colour (4,2), flavor (4,6) and taste (4,8). Based on the analysis of varian paired (Repeated ANOVA Test) with5% value of significance level( p< 0,05 ) obtained there was the difference in quality among the samples in terms of colour, flavor, taste and texture. This recommended cookies 2 as cookies with ideal criteria for a supplementary snack selection to donate and maintain the nutrient status. Keywords: cookies, beads flower rhizome, catfish, organoleptic assessment